Oxidative stress on vessels at the maternal-fetal interface for female reproductive system disorders: Update - Zhang, Chenlu; Guo, Yaxin; Yang, Yan; Du, Zhaojin; Fan, Yunhui; Zhao, Yin; Yuan, Suzhen (Frontiers in Endocrinology, 2023)
At present, many studies have confirmed the correlation between oxidative stress and female reproductive system diseases. However, there are few reviews focused on the effect of oxidative stress on blood vessels and the possible outcomes at the maternal-fetal interface. In order to provide an option for early clinical prediction and therapeutic application of oxidative stress in female reproductive system diseases, this paper briefly describes the composition of the maternal-fetal interface and the molecular mediators produced by oxidative stress, focuses on the sources of oxidative stress and the signaling pathways of oxidative stress at the maternal-fetal interface, expounds the adverse consequences of oxidative stress on blood vessels, and deeply discusses the relationship between oxidative stress and some pregnancy complications and other female reproductive system diseases.